Growth, Yield and Quality of Rabi Sunflower as Influenced by Moisture Absorbents, Organic and Inorganic Fertilizers - Bhusari, S. A.; Ghotmukale, A. K.; Jadhav, D. B.; Suryawanshiand, S. B.; Gaikwad, S. R. (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was carried out at Experimental Farm,Oilseeds Research Station, Latur to study the yield attributes ofwinter sunflower as influenced by absorbents, organic and inorganic fertilizers during the year of winter season 2016. The experimental field was uniform and levelled. The soil was black in colour low in available nitrogen (201.20 kg ha-1), low in available phosphorus (15.90 kg ha-1), high in available potash (483.80) and organic carbon (0.55%) withalkaline in reaction.The gross and net plot size were 5.4×4.8 m2 and 4.2×4.2 m2 respectively. There were seven treatment viz. RDF (90:45:45) NPK Kg ha-1, RDF+FYM @ 5 t ha-1, RDF+FYM @ 2.5 t ha-1, RDF+Hydrogel @ 2.5 kg ha-1, RDF+Humic acid @ 2.5 kg ha-1), RDF+Vermicompost @ 2.5 t ha-1 and RDF+Fly ash @ 2 t ha-1 which replicated thrice in Randomised Block Design. Data presented in Table 1 revealed that higher values of growth attributes i.e. plant height (205.37), No of leaves plant-1 (26.20), Dry matter plant-1 (146.50 g), Stem girth (9.13 cm), leaf area (75.68 dm2), head diameter (12.93 cm), seed yield (1770 kg ha-1) due to the treatment of RDF+Hydrogel @ 2.5 kg ha-1. The result indicated that, the higher number of filled seeds plant-1 (841.67), seed yield plant-1 (41.76 g ), test weight (54.33 g), harvest index (36.67%), seed yield (1770 kg ha-1), oil content (37.97%), oil yield (672.06 kg ha-1) by the application of RDF along with hydrogel @ 2.5 kg ha-1. The highest stalk yield (4031.54 kg ha-1) was observed with RDF (90:45:45 NPK kg ha-1).